Tinjauan Yuridis Kedudukan Janda/Duda sebagai Ahli Waris Golongan I: Antara Keadilan Filial dan Kesejahteraan Pasangan - Rayi Kharisma Rajib; Excellino Sagara Salim Putra; Yusuf Attar Mahang (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Legal uncertainty in inheritance distribution in Indonesia stems from the simultaneous application of three inheritance law systems without a clear hierarchy. This study aims to analyze the legal position of widows and widowers as first-class heirs from the perspective of filial justice and to formulate an ideal model of family protection norms following the death of a spouse. The method employed is normative juridical research utilizing statutory, conceptual, and comparative approaches. The findings indicate that filial justice has not been applied consistently across the three legal systems, as reflected in the inconsistency of Supreme Court jurisprudence. This study proposes a proportional-contributive reconstruction model integrating contributive proportionality, minimum protection for the surviving spouse, and guaranteed filial justice, positioning both values as mutually reinforcing pillars within a coherent inheritance law framework.